Daylight Saving Time and Artificial Time Zones – A Battle Between Biological and Social Times - Roenneberg, Till; Winnebeck, Eva C.; Klerman, Elizabeth B. (Frontiers in Physiology, 2019)
Many regions and countries are reconsidering their use of Daylight Saving Time (DST) but their approaches differ. Some, like Japan, that have not used DST over the past decades are thinking about introducing this twice-a-year change in clock time, while others want to abolish the switch between DST and Standard Time, but don’t agree which to use: California has proposed keeping perennial DST (i.e., all year round) and the EU debates between keeping perennial Standard Time or perennial DST. Related to the discussion about DST is the discussion to which time zone a country, state or region should belong: the state of Massachusetts in the US is considering switching to Atlantic Standard Time, i.e., moving the timing of its social clock (local time) one hour further east (which is equivalent to perennial DST), and Spain is considering leaving the Central European Time to join Greenwich Mean Time (GMT), i.e., moving its social timing one hour further west. A wave of DST discussions seems to periodically sweep across the world. Although DST has always been a political issue, we also need to discuss the biology associated with these decisions because the circadian clock plays a crucial role in how the outcome of these discussions potentially impact our health and performance. Here we give the necessary background to understand how the circadian clock, the social clock, the sun clock, time zones and DST interact. We address numerous fallacies that are propagated by lay people, politicians, and scientists, and we make suggestions of how problems associated with DST and time-zones can be solved based on circadian biology.